Pengaruh Lingkungan Kerja Terhadap Turnover Intention Karyawan Di Toko Arham Elektronik Tasiu - Syahra Ruslan; Agus Halim (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze the effect of the work environment on employee turnover intention at Arham Elektronik Store Tasiu. The study adopts a qualitative descriptive approach using literature review and secondary data analysis without direct field research. Data were obtained from national and international journals published within the last five years, relevant books, and reports related to human resource management, particularly work environment and turnover intention. The findings indicate that the work environment significantly influences employee turnover intention, both in physical and non-physical aspects. An unconducive work environment, lack of safety, low comfort, poor interpersonal relationships, and weak managerial support tend to increase employees' intention to leave the organization. Conversely, a supportive and comfortable work environment helps reduce turnover intention. This study concludes that effective work environment management is a key strategy for small and medium retail businesses to retain employees and maintain operational stability.